determinants of social exclusion in indigenous peoples and nationalities of ecuador in 2023 - Marchán Maldonado, Jerónimo Francisco (2024)
Ecuador, a diverse and plurinational country, is home to several ethnic groups, including indigenous peoples and nationalities, who are the most affected by income and multidimensional poverty, both phenomena related to social exclusion. This exclusion refers to ceasing to be a full citizen due to lacking fundamental and instrumental freedoms. The research examines the determinants that explain social exclusion in indigenous peoples in 2023. Using descriptive statistics, a multidimensional indicator, and Logit models, it was determined that 44.27 % of the Indigenous population suffers from exclusion. Being Indigenous, especially if they live in rural areas, are women, over 18 years of age, are disabled, are dedicated to agriculture or livestock, and live in the Amazon increases this probability. Unlike earlier studies, we found that Indigenous minors are less prone to exclusion, which could respond to public policies focused on their development. The results might guide programs that improve the living conditions of the indigenous ethnic group, prioritizing food, infrastructure, and education.